The Effect of Improving Human Resources for Student Interest in Selecting University on Food Security and Health: Structural Equation Modeling (SEM) - Justin Eduardo Simarmata; Ferdinandus Mone; Debora Chrisinta; Winda Ade Fitriya B (RANGE: Jurnal Pendidikan Matematika, 2024)
The selection of State Universities by students has a significant impact on improving the quality of human resources, so it can also affect the improvement of food security and health. This study aims to understand the extent of students' interest in selecting university which contributes to improving human resources and can indirectly affect food security and health. This study uses the Structural Equation Modeling (SEM) method to analyze the interaction between latent variables. Data was collected through questionnaires from high school students on the Indonesia-Timor Leste border. The data used in this study include students' interest in selecting university (Y), education and knowledge (X1), skills and abilities (X2), food security (X3), and health (X4). The results showed that students' interest in selecting university had a significant correlation with improving human resources through education by 90% (X1) and 84% (X2). The impact of this increase in human resources is also seen in the improvement of food security and public health which provides a correlation of 98% (X3) and 81% (X4).